PENGARUH BRAND IMAGE, PROMOSI DIGITAL DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN SEPATU NIKE (STUDI KASUS MAHASISWA DI UNIVERSITAS WIJAYA KUSUMA SURABAYA) - Daffa Rizq Marsiponga; Adrianto Trimarjono (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the influence of brand image, digital promotion, and lifestyle on the purchasing decisions for Nike shoes among students of Wijaya Kusuma University Surabaya. This research employs a quantitative approach with an explanatory research method. Data were obtained by distributing questionnaires to 64 respondents who are active students of Wijaya Kusuma University Surabaya and have purchased Nike shoes. The sampling technique used was purposive sampling. The data analysis methods used include validity tests, reliability tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). The results indicate that partially, brand image, digital promotion, and lifestyle have a positive and significant influence on the decision to purchase Nike shoes. Simultaneously, these three independent variables also have a significant influence on purchasing decisions. The lifestyle variable has the most dominant influence compared to the other variables. These findings suggest that the alignment between Nike's brand image, digital promotion strategies, and student lifestyles plays a crucial role in driving purchasing decisions. This research is expected to serve as a consideration for the company in formulating more effective marketing strategies and as a reference for future studies